Mixed Adeno and Neuroendocrine Carcinoma of The Ovary: Case Report - KADE YUDI SASPRIYANA; I NYOMAN BAYU MAHENDRA; KETUT SUWIYOGA; LUH PUTU IIN INDRAYANI MAKER; JOHANA SENSY LENI MANNA (Indonesian Journal of Cancer, 2017)
Reporting two cases of mixed adenocarcinoma and neuroendocrine carcinoma of the ovary. A case report two cases of an ovarian cyst suspect malignancy after complete surgical staging in woman aged 39 year old and 72 year old. By this case report, we want to know prognosis of the malignancy. Mixed adenocarcinoma and neuroendocrine carcinoma of the ovary of the first case arised from mature cystic teratoma, and second case as metastatic process from gastrointestinal tract. Mixed adenocarcinoma and neuroendocrine carcinoma is rare hystologic type of ovarian cancer. Need further exploration to know the survival of this hystologic type.ABSTRAKArtikel ini melaporkan dua kasus, yaitu mixed adenocarcinoma dan neuroendocrine carcinoma ovarium, dua kasus kista ovarium curiga ganas pada pasien berusia 39 tahun dan 72 tahun. Terhadap kedua pasien dilakukan komplit surgical staging. Melalui laporan kasus ini, diharapkan bisa diketahui prognosis kasus. Mixed adenocarcinoma dan neuroendocrine carcinoma ovarium pada kasus pertama timbul dari teratoma matur kistik, sedangkan kasus kedua merupakan penyebaran dari traktus digestivus. Mixed adenocarcinoma dan neuroendocrine carcinoma merupakan tipe histologi kanker ovarium yang jarang. Ia membutuhkan eksplorasi lebih lanjut untuk mengetahui survival dari tipe histologi ini.